The use of CT scan imaging technique to determine pear bruise level due to external loads. Issue 1 (20th November 2018) - Azadbakht, Mohsen; Vahedi Torshizi, Mohammad; Mahmoodi, Mohammad Javad
Abstract: X‐ray computed tomography (CT) is an effective noninvasive tool to visualize fresh agricultural commodities' internal components and quality attributes, also imaging via X‐ray CT is a non‐destructive and well‐developed method applied in measuring the internal effects of agricultural products. In the present research, 120 healthy pears with their health verification through the CT were selected. Next, 81 healthy pears were selected and subjected to quasi‐static and dynamic loading. The impact of the incoming pressures was investigated within 5, 10, and 15 days of storage. After loading and storing with the use of CT method, the total volume and the bruise volume of the pears were measured and the ratio of the bruise volume to the volume of each pear was calculated. Quasi‐static loads were pressurized over a period of two ways; the pressure of wide edge was exerted at three force levels of 70, 100, and 130 N while the pressure of the thin edge was applied at 15, 20, and 25 N. Dynamic loading was performed by utilizing a pendulum and 300, 350, and 400 g mass. The results of the experiments indicated that in the quasi‐static loading, the maximum and minimum amounts of pear bruise were 45.138% and 0.094% of the fruit, respectively. Besides, in the case of thin edge pressures, the minimum and maximum bruise levels were 0.007% and 19.88%, respectively. These values were obtained through 5 and 15 days of storage, respectively. In the dynamic loading, the maximum and minimum amounts of pear bruise were 47.36% and 0.21% of the total fruit, respectively, occurring at 400 and 300 g mass impact. Abstract : When a pear is affected by wide edge (pear‐to‐pear) pressure in the shipping box, or in the store or fruit shop, it is best to be used within 6–9 days. If a pear is affected by thin edge pressure, exerted by the corners of the fruit boxes, it is better to be used within 10 days. If a pear is affected by impact from falling down a tree or human treatment, it is best to be used in less than 15 days.